Dudka A.M., Kuzyayev I.M., Nachovny I.I., Burya O.I., Tkachenko E.V., Tolstenko Yu.V. Application of computer programs for reception of approximation equations investigation of tribotechnical properties of composites. - Дудка, А. М.; Кузяєв, І. М.; Начовний, І. І.; Буря, О. І.; Ткаченко, Е. В.; Толстенко, Ю. В. (Problems of Tribology, 2018)
Under considerations questions about development of polymeric compositional materials based on Teflon with fiber (carbon fiber made from Urals fabric) and disperse fillers (bentonite, graphite GK-1, dioxide of the titan). It had been investigated their tribotechnical properties and established basic dependence between it and service conditions of this materials in friction units. It had been investigate wear resistance of this material on friction machine МDP-1 by the friction without oiling with velocity V = 0,3 m/s and loadings Рп = 1 МPа. It had been established optimal composition of development polymeric compositional materials for friction of chemical equipment. Experimental data had been processed by means of the MathCAD 11 program. It had been obtained analytical equation, which describes dependence of friction coefficient by velocities and loadings in friction units. It had been investigations of the dependence of friction coefficient by temperature in friction units of machine and mechanism.